2014
DOI: 10.1371/journal.pone.0086514
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Dialysis Systolic Blood Pressure-Variability Is Independently Associated with All-Cause Mortality in Incident Haemodialysis Patients

Abstract: Systolic blood pressure variability is an independent risk factor for mortality and cardiovascular events. Standard measures of blood pressure predict outcome poorly in haemodialysis patients. We investigated whether systolic blood pressure variability was associated with mortality in incident haemodialysis patients. We performed a longitudinal observational study of patients commencing haemodialysis between 2005 and 2011 in East Anglia, UK, excluding patients with cardiovascular events within 6 months of star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 21 publications
0
29
1
1
Order By: Relevance
“…These remain, however, less well-investigated in hemodialysis patients. SD, CV and VIM were recognized as the most common BPV metrics [3, 4, 12, 14],but no evidence supporting which one is better. The ROC curves showed no difference among the three metrics in predicting the mortality (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These remain, however, less well-investigated in hemodialysis patients. SD, CV and VIM were recognized as the most common BPV metrics [3, 4, 12, 14],but no evidence supporting which one is better. The ROC curves showed no difference among the three metrics in predicting the mortality (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were obtained immediately before, after, and during each dialysis session from January 1, 2006 to December 31, 2006. Raw BPs were transformed into the following 3 candidate BPV metrics, which are widely used in BPV studies [3, 4, 12, 14]: the standard deviation (SD), the coefficient of variation (CV), and the variation independent of the mean (VIM). VIM is a transformation of the standard deviation that is uncorrelated with mean BP and is calculated as follows:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that visit-to-visit BPV is extremely high in HD patients than non-HD populations and is a strong predictor for cardiovascular events [45]. Pre-dialysis systolic BPV is also associated with cardiovascular and all-cause mortality [46][47][48]. Not only pre-dialysis BPV but also intra-and post-dialysis BPV are related to adverse outcomes.…”
Section: Considerations For Blood Pressure Variability (Bpv)mentioning
confidence: 99%
“…Some studies demonstrated that visit-tovisit BP variability was a novel risk factor for stroke (3), cardiovascular events (3), and all-cause mortality in the general population (6). It is reported that visit-to-visit BP variability also predicted cardiovascular events and allcause mortality in patients with chronic kidney disease (7,8) and hemodialysis (5,(9)(10)(11)(12)(13)(14). Note, however, that different dialysis modalities should have different effects on BP due to the intermittent nature of hemodialysis and continuous nature of peritoneal dialysis (PD).…”
Section: Introductionmentioning
confidence: 99%